The Influence of Product Completeness on Consumer Purchasing Decisions at Kicau Kecil Baby Kids Store Tangerang Selatan Branch - Nurochani, Nila (Kompartemen: Kumpulan Orientasi Pasar Konsumen, 2023)
This study aims to determine the effect of product completeness on purchasing decisions at Kicau Kecil Baby Kids Store, South Tangerang Branch. The method used is explanatory research with a sample of 100 respondents. The analysis technique uses statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this research variable product completeness obtained an average score of 3.41 with good criteria. Purchasing decision variable obtained an average score of 3.84 with good criteria. Product completeness has a significant effect on purchasing decisions with the regression equation Y = 9.730 + 0.842X, and a correlation value of 0.784 or strong with a determination of 61.5%. The hypothesis test obtained a significance of 0.000 <0.05.